KETERLIBATAN PEMERINTAH DAERAH DALAM PENGEMBANGAN PENDIDIKAN TINGGI (FENOMENA DI PROVINSI MALUKU) - Ismail DP; Saidin Ernas; Marwan Razak; Abidin Wakano (IAIN Ambon, 2022)
The existence of private higher education in the regions in this era of decentralization is a dilemma. On the one hand, they need local government assistance to grow and develop in order to contribute to regional development, but on the other hand the local government cannot help optimally because various existing regulations are hampered. This makes the local government to help universities in the region in various ways and without clear standards. After examining this phenomenon in Maluku, this study found several interesting findings. First, basically the regional government has tried to be involved in the development of higher education in the regions, but in terms of providing assistance there is no clear policy standard. Assistance provided by local governments is often based on the